Emergencies in critical care - Beed, Martin; Sherman, Richard (Consultant in critical care and anaesthesia); Mahajan, Ravi P. (Emergencies in-- series., 2013)
This essential handbook provides a practical, accessible guide to all emergency situations encountered in the critical care setting. Emergencies are very common in the critical care setting and this book helps critical care staff identify patients at risk, how to manage them, and be prepared. To help the reader find advice quickly, most chapters begin with a generic description of how to manage emergencies affecting that system, or patient group. This is followed by details ofspecific diagnoses and how they should be managed. The author team, where possible, follow the 'ABC' approach, which is.